2016
DOI: 10.1038/srep33277
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cell-cell fusion by nanotopography

Abstract: Cell-cell fusion is fundamental to a multitude of biological processes ranging from cell differentiation and embryogenesis to cancer metastasis and biomaterial-tissue interactions. Fusogenic cells are exposed to biochemical and biophysical factors, which could potentially alter cell behavior. While biochemical inducers of fusion such as cytokines and kinases have been identified, little is known about the biophysical regulation of cell-cell fusion. Here, we designed experiments to examine cell-cell fusion usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 63 publications
4
21
1
Order By: Relevance
“…However, the calculated roughness indicated that the surfaces were rather flat since adsorbed material was raised from the surface by ∼10 nm or less. Therefore, consistent with previous work [23, 30, 31], this study observed no clear connection between nanoscale (<100 nm) surface roughness and increased fusion. Although FD surface roughness was ∼2.5-fold higher than paraffin-adsorbed surfaces, the latter was significantly more active.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, the calculated roughness indicated that the surfaces were rather flat since adsorbed material was raised from the surface by ∼10 nm or less. Therefore, consistent with previous work [23, 30, 31], this study observed no clear connection between nanoscale (<100 nm) surface roughness and increased fusion. Although FD surface roughness was ∼2.5-fold higher than paraffin-adsorbed surfaces, the latter was significantly more active.…”
Section: Discussionsupporting
confidence: 89%
“…Interfacial processes driven by the physicochemical properties of the material are known to be important modulators of macrophage fusion [4, 23, 24]. In order to gain insight into the characteristics of the surface that might promote macrophage fusion, we employed atomic force microscopy (AFM) to directly visualize surface features.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, a hydrophilic titanium surface with nanotopography (modSLA) has been shown to modulate the early inflammatory response in vivo promoting polarization of macrophages to an M2-like phenotype, even in diabetic conditions where an exaggerated pro-inflammatory environment is a distinguishing feature (Lee et al, 2017). Titanium surface nanotopography has also been shown to regulate both macrophage cell shape (McWhorter, Wang, Nguyen, Chung, & Liu, 2013), the release of cytokines (Luu, Gott, Woo, Rao, & Liu, 2015) and restrict cytoskeletal remodelling-associated signalling by macrophages leading to reduced cell to cell fusion, potentially moderating the foreign body reaction (Padmanabhan et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The FBR to implants begins immediately after injury to tissue and, in the case of most synthetic implants, results in a variety of tissue responses including: recruitment of inflammatory cells to the surface of the implant, macrophage fusion to form foreign body giant cells (FBGCs), and eventual encapsulation in an avascular, oriented collagenous capsule . Biomaterial‐host interfaces have been the subject of countless studies over decades of work, which have led to the development of promising technologies that are able to promote specific biological responses from a variety of implants . Nevertheless, implants that do not degrade rapidly are ultimately subject to the FBR and fibrotic encapsulation.…”
Section: Introductionmentioning
confidence: 99%